STUDENTS’ ABILITY IN WRITING PART OF SPEECH REGISTERED 2019/2020 AT FORT DE KOCK UNIVERSITY BUKIT TINGGI - Hendra Putra; Mustakim Sagita (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The title of this research is students’ ability in writing part of speech registered 2019/2020 at Fort De Kock University, teaching english course in public health department, midwifery department, physiotherapy department, nursing department and bussiness digital department at Fort De Kock University Bukittinggi. The problem in this reserach is what is students’ ability in writing part of speech registered 2019/2020 at health faculty. The purpose of this research is to know students’ ability in writing part of speech. Part of speech refers to noun, pronoun, adjective, interjection, conjunction, preposition adverb and verb. This research uses descriptive method. It means that researcher describes the students’ ability as reality. Population of this research is public health and nursing students semester 1 of fort de kock university registered 2019/2020. The students have learnt about part of speech. Sample of this research is purposive sampling. It means that the researcher choose the participants or samples to be be researched, and also based on researcher need and researche question. The total of the sample is 51 students or participants. Collecting data is done by using writing test. The students re-write what have been seen in the question sheet. Then, reseracher asks students to re write in the answer sheet. In the answer sheet is provided for students to answer it. Then, it is analyzed whats’ students ‘ ability in writing part of speech. Based on the result found that students’ ability in writing part of speech is various. Students ability in writing noun, verb, adjective, adverb and cnjunction are good. Students ability in writing preposition is sufiicient. And students’ ability in wrting interjection is very good. It means that generally students have ability in writing interjection